2002
DOI: 10.1067/mhn.2002.125755
|View full text |Cite
|
Sign up to set email alerts
|

Skull Base Cerebrospinal Fluid Fistulas: A Comprehensive Diagnostic Algorithm

Abstract: For patients with skull base CSF fistulas, a graduated diagnostic approach with emphasis on confirmation of leak by beta2-transferrin analysis and precise localization by high-resolution computed tomography is both efficacious and cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(162 citation statements)
references
References 16 publications
1
141
0
16
Order By: Relevance
“…Starting with the simplest diagnostic tool and progressing to the most complex appears to be the most efficient and cost-effective route (Table 2). 119 While embarking on the treatment of these fistulas, we must remember that 85% of CSF rhinorrhea cases resulting from head trauma stop spontaneously and that the risk of meningitis is 0.68% in the first 24 hours after injury and increases up to 18.87% in the first 2 weeks after injury. 42,88 Published reviews have not shown that prophylactic treatment with antibiotics makes a difference, and therefore such therapy should be discouraged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting with the simplest diagnostic tool and progressing to the most complex appears to be the most efficient and cost-effective route (Table 2). 119 While embarking on the treatment of these fistulas, we must remember that 85% of CSF rhinorrhea cases resulting from head trauma stop spontaneously and that the risk of meningitis is 0.68% in the first 24 hours after injury and increases up to 18.87% in the first 2 weeks after injury. 42,88 Published reviews have not shown that prophylactic treatment with antibiotics makes a difference, and therefore such therapy should be discouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been done exclusively to assess the accuracy of HRCT in posttraumatic CSF leaks. In a retrospective review of 47 cases of traumatic and nontraumatic CSF leaks visualized on HRCT, Zapalac and colleagues 119 reported a sensitivity and an accuracy of 87% each. Yilmazlar and colleagues 118 reviewed 81 patients who were treated for CSF leakage due to skull base fractures.…”
Section: Diagnosis Of Csf Rhinorrheamentioning
confidence: 99%
See 1 more Smart Citation
“…This communication or fistula must involve a breech of the arachnoid and dura matter, the bone of skull base, and the underlying mucosa [1]. CSF rhinorrhea can be classified according to the etiology into traumatic and non-traumatic [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, high resolution CT is the fi rst line imaging technique, having a reported sensitivity ranging from 50% up to 100% (Dietrich et al 1993;Lloyd et al 1994, Zapalac 2002. It is obtained without intrathecal or intravenous contrast agent administration, using thin (1-or 2-mm) contiguous axial and coronal planes.…”
Section: Csf Leak Associated With Persistent or Intermittent Rhinorrheamentioning
confidence: 98%